The Effect of Storage Time on the Dimensional Stability of Zinc Oxide Eugenol Impression Material Under Dry and Moist Conditions - An In- Vitro Study - Limbu, IK; Pathak, B; Basnet, BB (Journal of Nepalese Prosthodontic Society, 2022)
Introduction: Accurate impression is an important factor to fabricate accurate dental casts and ultimately accurate dental prostheses. Due to time constraints, sometimes there is need of storing impression for some time which may alter the dimension. The objective of this study was to evaluate the dimensional stability of zinc oxide eugenol impression paste at different time intervals and in two conditions, dry and wet storage. Methods: Sixty study molds of zinc oxide eugenol impression material were prepared according to American dental Association specification no 19 for non-aqueous elastic dental impression materials and the distance between two specific lines were measured at different time intervals. The paired t test was utilized to assess the difference in mean dimension of the molds from specified time to the original measurement immediately after setting. Results: In dry storage condition, the dimensional changes were not seen up to 24 hours, but at 36 hours, there is statistically significant dimensional change. In wet condition, there was significant change in dimension after 6 hours onwards. Conclusion: The dimensional change was not significant up to 24 hours in dry condition. Thus, it can be poured up to 24 hours after setting. Dimensional stability was not seen after 6 hour and hence is recommended to pour within 30 minutes if kept under wet condition.